Paternalistic Leadership and Organizational Commitment - Hakimian, Fatemeh; Farid, Hadi; Ismail, Mohd Nazari; Ismail, Ismi Arif (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
In the competitive world of business, organizational commitment is considered to be one of the fundamental organizational issues facing managements. Committed employees have become a valuable contribution to a variety of organizations. Since leaders’ behaviors play an important role in organizational commitment, managers are encouraged to motivate employees to strengthen their commitments to competently serve their organizations. The structures of societies in addition to cultural values are influential factors in determining appropriate leader behaviors. Since Paternalistic leadership is an integrated part of Asian organizations, Malaysia was selected as the country of choice to conduct this study. This research was designed to investigate the relationship between paternalistic leadership and organizational commitment; Each dimension was investigated separately in accordance to quantitative methodology. In total, 287 questionnaires from the employees of Malaysian SMEs were selected to be used for the purpose of data analysis. Data management and analysis were performed using SEM-PLS. The statistical results indicated the significant relationship between paternalistic leadership and Affective, Continuance, and Normative Commitment. Paternalistic leadership is a significantly persuasive factor that elevates the phenomenal of affective and normative commitment. This finding also came to the attention that under the umbrella of Paternalistic leadership, distress of losing a specific leader might be a determining factor for employees to continue their cooperation and employment with the organization. In addition to offering theoretical contributions, this study has provided a practical guideline for Malaysian SMEs managers who aim to increase commitment among employees who function under their Paternalistic leadership.